The Effect of Plyometric and Extensive Interval Training Methods on the Accuracy of Jumping Smash Athletes of the Badminton Association of Padang City - Muharsyad Al Azip; Syamsuar Syamsuar; Syafruddin Syafruddin; Masrun Masrun (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effect of pliometrik training methods and extensif intervals on increasing the accuracy of the jumping smash of PB Reta Utama athletes in Padang City. This study uses an experimental method with a